Sudden Cardiac Arrest in a Youth with Multiple Arrhythmic Substrates - James Ainsworth; Adrian Ionescu (Case Reports in Critical Care)
Background. Mitral valve prolapse (MVP) is a common condition with an estimated prevalence of 1-3%, in which there is systolic displacement of a morphologically redundant mitral valve towards the left atrium. Mitral annular disjunction (MAD) is a separation of the MV attachment with the left ventricle, with hypermobility of the leaflets, and with systolic “curling” of the basal LV (left ventricle) myocardium. It is frequently associated with MVP and may confer an increased arrhythmic risk. Case Description. A 28-year-old male had ventricular fibrillation leading to out-of-hospital cardiac arrest, which was successfully resuscitated. His coronary arteries were unobstructed on invasive coronary angiography. Transthoracic echocardiogram (TTE) demonstrated MAD, confirmed by cardiac magnetic resonance (CMR) imaging and transoesophageal echocardiogram (TOE). The LV was severely dilated with reduced EF (ejection fraction), and the QTc interval was also prolonged. His father had died suddenly aged 50 years. Conclusions. This report describes the clinical dilemma of identifying and treating a patient with multiple potential causes of cardiac arrest. Despite being relatively common, the clinical significance of MAD is still uncertain and the extent to which it may be linked with complications such as ventricular arrhythmias and sudden cardiac death. MAD appears to confer an increased risk of ventricular arrhythmias, particularly when associated with MVP, particularly nonsustained VT.